In Vitro Evaluation of Biological Activities of Canes and Pomace Extracts from Several Varieties of Vitis vinifera L. for Inclusion in Freeze-Drying Mouthwashes - Anca Pop; Catalina Bogdan; Ionel Fizesan; Sonia Iurian; Rahela Carpa; Cecilia Bacali; Laurian Vlase; Daniela Benedec; Mirela L. Moldovan (Antioxidants, 2022)
In this study, the biological activities of four extracts from Vitis vinifera by-products: two pomace extracts, white (WPE) and red (RPE), a canes extract (CE), and their combination (CoE), were evaluated, to be included in freeze-drying mouthwashes formulations. The cytocompatibility and anticancerous potential of the four extracts were tested on three cancerous cell lines, as well as the cytoprotective activity against nicotine-induced cytotoxicity and the antioxidant potential determined on a human gingival fibroblasts (HGF) cell line. Additionally, the anti-inflammatory activity and the antimicrobial activity against several microorganisms from the oral microbiome were tested. Freeze-dried mouthwashes with CoE were prepared and characterized, both as lyophilizates and after reconstitution. The four tested extracts showed the highest cytotoxicity on MDA-kb2 cell line. The antioxidant potential was demonstrated for WPE, RPE, CE, and CoE, both in non-stimulated and H2O2 stimulated conditions. The four extracts reduced the levels of proinflammatory cytokines (IL-6, IL-8, and IL-1β) in a dose-dependent manner, confirming their anti-inflammatory activity. The antimicrobial activity of tested extracts was shown against pathogenic bacteria from the oral microbiome. Mouthwashes of CoE with poloxamer-407, xylitol, and different ratios of mannitol were prepared by freeze-drying leading to porous formulations with interesting mechanical properties and reconstitution times.